Analysis of Female Labor Force Participation (FLFP) in East Java - Tsaniyah, Alfi Hakimatus; Sugiharti, Lilik (Department of Economics, Faculty of Economics and Business, Universitas Airlangga, 2021)
Employment has an important role to support a certain economy. The number of female workers have increased every year, due to family welfare fulfillment and female role shifting as a head of households. This paper aims to observe the driving factors of female labor force participation in East Java-Indonesia. Logit model is incorporated to estimate the parameters which involved total sample of 23.218 women in productive age which consist of 13.473 working women and the rest of 9.745 non working women in East Java. On the basis of micro data level from National Labor Force Survey (Sakernas) 2018, the result shows that age, education level, marital status, head of the household status, household size, rural-urban location, and income have a substantial effect on FLFP in East Java. Keywords: FLFP, Employment Status, Work Decision, Logit Model. JEL: J01, J20, J21